Molecular Cloning - Dincer, Sadık; Aysun Mercimek Takcı, Hatice; Sumengen Ozdenef, Melis (IntechOpen, 2022)
This book examines the fundamentals of molecular cloning and molecular cloning applications in various areas. Chapters address such topics as tools and methodologies of molecular cloning, molecular cloning for medicine, food and feed, the environment, and the future of molecular cloning.